1998
DOI: 10.1007/s002449900424
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants in Ospreys from the Pacific Northwest: I. Trends and Patterns in Polychlorinated Dibenzo- p -Dioxins and -Dibenzofurans in Eggs and Plasma

Abstract: Osprey (Pandion haliaetus) eggs were collected from 1991 to 1997 at nests (n = 121) upstream and downstream of bleached kraft pulp mills and at reference sites in the Fraser and Columbia River drainage systems of British Columbia, Washington, and Oregon. Blood samples were collected from nestling ospreys during the 1992 breeding season on the Thompson River. Samples were analyzed for polychlorinated dibenzo-p-dioxins (PCDDs) and -dibenzofurans (PCDFs). Mean concentrations of 2,3,7,8-TCDD were significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
43
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 32 publications
8
43
0
Order By: Relevance
“…65 More than 25% of sampled eggs exceeded the toxicity threshold of 4.2 μg/ g, and the spatial pattern was not explained by known local sources and partially prompted use of satellite telemetry to examine wintering sources. 24 The rapid melting of glacial ice The decline in concentrations of ΣDDT and ΣPCBs in osprey eggs over the period 1991 to 2003 at one of our monitoring sites is shown in SI Figure S4. Kamloops is a river location which does integrate runoff from the surrounding alpine drainage basin.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 More than 25% of sampled eggs exceeded the toxicity threshold of 4.2 μg/ g, and the spatial pattern was not explained by known local sources and partially prompted use of satellite telemetry to examine wintering sources. 24 The rapid melting of glacial ice The decline in concentrations of ΣDDT and ΣPCBs in osprey eggs over the period 1991 to 2003 at one of our monitoring sites is shown in SI Figure S4. Kamloops is a river location which does integrate runoff from the surrounding alpine drainage basin.…”
Section: ■ Discussionmentioning
confidence: 99%
“…24 Each bird was weighed, measured, and banded with a U.S. Fish and Wildlife Service band on one leg and a red alphanumeric band on the other leg.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Some otters with higher concentrations of total H6CDD, total H7CDD and OCDD may have been exposed to PCP, a wood preservative from which higher chlorinated PCDDs and PCDFs are present as impurities (Schwetz et al 1974;Goldstein et al 1977;Elliott et al 1999). Elliott et al (1998) also reported a significant relationship between PCP and OCDD in osprey eggs from an area of heavy chlorophenolic use. The unusually high TCDD (506 ng kg −1 ) and OCDD (1521 ng kg −1 ) concentrations for the juvenile male trapped west of Chehalis, WA was exposed locally since that age class had not dispersed.…”
Section: Pcbsmentioning
confidence: 90%
“…Compared with northern breeding sites, relatively little is known about contaminant exposure in the overwintering areas of many migratory species, such as the Osprey Pandion halieatus (Elliott et al 1998(Elliott et al , 2000(Elliott et al , 2007. Similarly, compared with the extensive data base on Hg in fish, largely collected as part of game fish monitoring in the United States and Canada (Kamman et al 2005;Davis et al 2008;Wyn et al 2010), there is much less from wintering areas in Mexico and Central America, with some exceptions (Mol et al 2001;RuelasInzunza and Páez-Osuna 2005).…”
mentioning
confidence: 92%